CAD Algorithm for Calculating the Constant DC Load of a Substation Battery Unit - Panova, Evgeniya A.; Varganova, Aleksandra V.; Sorokin, Nikita S. (2020 International Russian Automation Conference (RusAutoCon), 2020)
The uninterrupted operation of the DC system of the step-down substation ensures the reliable functioning of not only the substation and its consumers, but also the whole node of the electric network. Reliable operation of the DC system is ensured not only by the selection of its reliable elements and power source (battery), but also by the quality of the design. Most of the work in this area are aimed at solutions for protecting DC systems, modeling the modes of these networks and their application in distributed generation systems. Design issues are addressed in the form of recommendations developed by enterprises manufacturing electric storage batteries or enterprises operating this equipment. In this article, the authors had developed and applied in the original CAD of step-down substations the algorithm for the automated calculation of the load of a battery and the choice of its capacity. The proposed algorithm allows the designer to find out the required battery capacity based on information on switchgear circuits and the selected main electrical equipment. The work is carried out with the financial support of a grant from the President of the Russian Federation for young scientists - candidates of sciences MK-939.2019.8.